PROBLEMATIKA HUKUM ATAS PERNYATAAN PUTUS HUBUNGAN ANTARA ORANGTUA ANGKAT DAN ANAK ANGKAT - M A L I S A M A L I S A (PREMISE LAW JURNAL, 2015)
One of the goals in marriage is to get offspring, but sometimes a marriage which has taken place for a long time still does not have offspring. Some people then adopt children that are regarded as their own children as the substitute for the biological ones. In the Western Civil Law, this way is called adoption which is called by the researcher as adopting a child. In order that adopting a child is properly registered, it must follow the legal process as it is stipulated in Chapter II of the Staatsblad No. 129/1917 on Adoption. In the Circulation Letter of the Supreme Court (SEMA) No. 6/1983 on Adoption, there is the amendment of the validity of adoption which states that not only by a Notary’s deed but also by the legal process in Court as the Ruling of the District Court. Therefore, a Notary plays an important role in legal protection for the inheritance rights for an adopted child of Chinese ethnic group as an Indonesian citizen. The breach of relationship between adoptive parents and their adopted child occurs when the child has already been an adult and does not comply with his adoptive parents’ counsels; for examples, he is a spendthrift, a gambler, and his behavior does not reflect what his adoptive parents have expected. The breach of relationship causes him to be unfaithful as the descendant and to inherit his adoptive parents’ wealth. Keywords: Breach of Relationship, Adoptive Parents, Adopted Child